Do right to work laws worsen income inequality? Evidence from the last five decades - Munasib, Abdul; Jordan, Jeffrey L.; Mathur, Aparna; Roy, Devesh (Agricultural and Applied Economics Association, 2015)
There is an ongoing debate about whether changes in labor regulations such as Right to Work (RTW) laws are contributing to the rising trend of income inequality in the U.S. We adopt Synthetic Control Method (SCM) for comparative case study to examine the impact of a state’s adoption of RTW law on its income inequality. We use a wide range of inequality measures for Idaho, Louisiana, Oklahoma and Texas, states that enacted RTW between the 1960s and the 2000s. We find that RTW did not impact income inequality in these states. This result is underpinned by additional finding of a lack of impact of RTW on unionization and investment. Munasib, Abdul; Jordan, Jeffrey L.; Mathur, Aparna; Roy, Devesh